2021
DOI: 10.3390/plants10102184
|View full text |Cite
|
Sign up to set email alerts
|

Genome-Wide Analysis and the Expression Pattern of the MADS-Box Gene Family in Bletilla striata

Abstract: Bletilla striata (Thunb. ex A. Murray) Rchb. f., a species of the perennial herb Orchidaceae, has potent anti-inflammatory and antiviral biological activities. MADS-box transcription factors play critical roles in the various developmental processes of plants. Although this gene family has been extensively investigated in many species, it has not been analyzed for B. striata. In total, 45 MADS-box genes were identified from B. striata in this study, which were classified into five subfamilies (Mδ, MIKC, Mα, Mβ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 67 publications
0
5
0
Order By: Relevance
“…To further investigate the function of the C2H2 zinc finger genes the cis-acting promoter regulatory elements were analyzed. Previous studies had shown that promoter cis-regulatory elements can be classified into five main functional groups: transcriptional, cell cycle, hormonal, abiotic or biotic stress, and developmental ( Mi et al, 2021 ).…”
Section: Resultsmentioning
confidence: 99%
“…To further investigate the function of the C2H2 zinc finger genes the cis-acting promoter regulatory elements were analyzed. Previous studies had shown that promoter cis-regulatory elements can be classified into five main functional groups: transcriptional, cell cycle, hormonal, abiotic or biotic stress, and developmental ( Mi et al, 2021 ).…”
Section: Resultsmentioning
confidence: 99%
“…Multiple sequence alignment of MADS gene sequences was performed using the ClustalX2 program with default parameters ( Katoh & Standley, 2013 ; Mi et al, 2021 ). The sweet orange MADS genes were renamed according to the gene position on the chromosome.…”
Section: Methodsmentioning
confidence: 99%
“…The number of motifs was set to 10, the minimum width of motifs was set to 6, and the maximum was set to 50. Other parameters were set by default [ 43 , 44 ]. We then downloaded the result meme.xml file and used the visualize meme/mast motif pattern tool of TBtools software_0987663 (Guangzhou, China) to visualize the results [ 45 ].…”
Section: Methodsmentioning
confidence: 99%